Compression behaviour of Q355 steel angles with local defect at bolt holes - Zhang, Jinglu; He, An; Liu, Yu; Kang, Shao-Bo (Frontiers in Materials, 2024)
This paper presents experimental and numerical studies on compression behaviour of equal-leg steel angles with bolted connection and subjected to local defect at the bolt hole. To simulate corrosion, a mechanical cutting method was used in the experimental test to increase the diameter of bolt holes, and a total of 18 steel angles were investigated in the study. The parameters considered included the slenderness and the diameter of bolt holes. The slendernesses of steel angles were 80 and 140, and the diameter of bolt holes ranged from 21.5 mm to 27.5 mm. Additionally, numerical models were established for the steel angles. The accuracy of the numerical model was verified by comparing experimental data with numerical results. Based on the validated numerical model, a parametric analysis was conducted to quantitatively assess the influences of the slenderness and the diameter of bolt holes on the load capacity of specimens against global buckling. Experimental and numerical results showed that the defect at the bolt hole affected the load capacity of specimens when the diameter of the bolt hole was increased to 27.5 mm and the slenderness was not greater than 100.